Is There an Energy Efficiency Gap in China? Evidence from an Information Experiment - Graham Beattie; Iza Ding; Andrea La Nauze (Center for Economic Studies and ifo Institute (CESifo), 2021)
We provide evidence of an energy efficiency gap in China. Using an incentivized field experiment, we document that providing information to consumers on the energy costs of lightbulbs significantly affects their willingness to pay for energy efficient bulbs. Unlike previous literature, we do not find evidence that this gap is driven by biased beliefs. Further our experimental design allows us to rule out that changes in willingness to pay are driven purely by the salience of the monetary or environmental costs of lightbulbs. We argue that the results are consistent with consumers being risk averse and uncertain about the benefits of more energy efficient appliances.
Keywords: Q40; H23; 330; energy-efficiency; lightbulbs; information experiment